Attention systems and the organization of the human parietal cortex - Rushworth, M; Paus, T; Sipila, P (Society for Neuroscience, 2001)
Event-related functional magnetic resonance imaging was used to compare activity in the human parietal cortex in two attention-switching paradigms. On each trial of the visual switching (VS) paradigm, subjects attended to one of two visual stimuli on the basis of either their color or shape. Trials were presented in blocks interleaved with cues instructing subjects to either continue attending to the currently relevant dimension or to switch to the other stimulus dimension. In the response switching (RS) paradigm, subjects made one of two manual responses to the single stimulus presented on each trial. The rules for stimulus-response mapping were reversed on different trials. Trials were presented in blocks interleaved with cues that instructed subjects to either switch stimulus-response mapping rules or to continue with the current rule. Brain activity at "switch" and "stay" events was compared. The results revealed distinct parietal areas concerned with visual attentional set shifts (VS) and visuomotor intentional set shifts (RS). In VS, activity was recorded in the lateral part of the intraparietal region. In RS, activity was recorded in the posterior medial intraparietal region and adjacent posterior superior and dorsomedial parietal cortex. The results also suggest that the basic functional organization of the intraparietal sulcus and surrounding regions is similar in both macaque and human species.